LAYANAN BIMBINGAN PRA PERKAWINAN DI INDONESIA: SYSTEMATIC LITERATURE REVIEW - Dhammanando *; Partono Nyanasuryanadi; Kabri * (Pascasarjana Universitas Hindu Indonesia, 2024)
Pre-marital guidance is still doubtful in its effectiveness in preparing prospective bridal couples towards a happy and prosperous family. The role of the government in supporting pre-marital guidance services greatly influences the implementation of this activity. Both from the support of funds and facilities for the continuity of pre-marital guidance to prospective brides according to their religion. This research uses the Systematic Literature Review (SLR) approach with the intention of providing an overview of pre-marital guidance services from various religions in Indonesia. The scientific literature taken was published from 2018 to 2023. After determining the inclusion and exclusion criteria from 500 articles obtained from POP (Publish or Perish), 10 relevant journal articles were selected for further analysis. The Systematic Literature Review method used in this study is to analyze and identify previous studies related to the topic of pre-marital guidance. Based on the selected primary literature, there is an increasing trend of pre-marital counseling services from previous years. It was also identified that the materials in pre-marital guidance that are most often given are: understanding of happy and prosperous marriage, mental preparation for marriage, communication techniques in the household, knowledge of the reproductive system and parenting system. There are three important components in the smooth running of pre-marital counseling services. The first is the government, in this case the KUA officer or P4K officer or pandita or pastor or priest. Second is the budget available for guidance services. The third is the facilities that support pre-marital guidance services. From the various journals analyzed, it was concluded that pre-marital guidance or counseling has a positive effect on family continuity and harmony.